Exploring the Antecedents of Money Attitudes in China: Evidence From University Students - Li, Yuqian; Hu, Fengfei (Frontiers in Psychology, 2022)
With the rapid economic growth and institutional reform, pursuing money and material possessions have become the most prevalent value in contemporary China. This study focuses on the cultural root of money attitudes among the young generation. Specifically, 332 Chinese university students participated in the survey to report their endorsement on need for power, need for achievement, belief in guanxi and love of money. Confirmatory factor analysis and regression analysis were applied to test the proposed hypotheses. The results show positive influences of need for power and need for achievement on individuals’ love of money. Moreover, belief in guanxi mediates the relationship between need for power and love of money. The application of indigenous cultural concepts in analyzing social behavior in Eastern cultures is emphasized. Limitation and directions for future research are also provided.